2015
DOI: 10.1097/ico.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Eye Comparison Between Femtosecond Small Incision Intrastromal Lenticule Extraction at Depths of 100 and 160 μm

Abstract: Creating the refractive lenticule at a depth of 160 μm in SMILE had less effect on the corneal biomechanics than did creating a lenticule at a depth of 100 μm with no statistically significant differences in the refractive outcome and THOA between both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…35 A contralateral eye study of myopic SMILE using a 100-or 160-lm cap thickness reported significantly lower values of CH and CRF in the 100-lm cap group; this may suggest a more pronounced decrease in the postoperative viscoelasticity. 23 However, the average cylindrical and spherical correction was slightly higher in the group with a 100-lm cap thickness, although no significant differences were reported between groups. The positive correlation between lenticule thickness and the average decrease in CH and CRF 36 may explain the difference reported between the 100-and 160-lm cap groups.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…35 A contralateral eye study of myopic SMILE using a 100-or 160-lm cap thickness reported significantly lower values of CH and CRF in the 100-lm cap group; this may suggest a more pronounced decrease in the postoperative viscoelasticity. 23 However, the average cylindrical and spherical correction was slightly higher in the group with a 100-lm cap thickness, although no significant differences were reported between groups. The positive correlation between lenticule thickness and the average decrease in CH and CRF 36 may explain the difference reported between the 100-and 160-lm cap groups.…”
Section: Discussionmentioning
confidence: 83%
“…23,32,33 One study evaluated the refractive outcome using cap thicknesses of 130, 140, 150, or 160 lm in patients with a mean preoperative spherical equivalent of À4.89 6 1.48 D. 32 The authors reported a 12-month postoperative undercorrection of À0.10 6 0.60 D (2%) and À0.17 6 0.25 D (3.5%) at a cap thickness of 130 or 160 lm, respectively. However, an intended overcorrection of 10% was performed in patients with a 160-lm cap thickness, because of possible energy loss due to a thicker cap.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations